Hemart Oil Purchase Decisions Required From Aspect Products, Brands And Price - Nugroho, Jemi (KELOLA, 2018)
The purpose of this study is to prove or show the results of significant purchasing decisions hemart oil in review of aspects of Products, Brands and Prices. Analytical technique in this research consist of instrument test: validity test and reliability test, classical assumption test, multiple linear regression analysis, t test, F test and R² test. Based on the results of this study can be seen that aspects of products, brands and prices have a positive effect on consumer purchasing decisions in oil hemart solo. The result of statistical test t shows that the Product has a positive and significant effect on the purchasing decision, Brand, has positive and significant influence on consumer purchasing decision and Price, positively and significantly influence to consumer purchasing decision at Hemart Solo Oil Distributor. F statistical test results can be concluded together product, brand and price variables have a significant influence on the purchase decision of hemart oil in solo. Adjusted R square test results obtained results of 0.692 which means the variability of consumer purchasing decisions on oil hemart in solo. able to be explained by product, brand and price variable equal to 69,2% while the rest 30,8% explained by other variable not participated observed. For example location, service, advertising and service procedures etc. The most dominant variable that influence Interest purchase is the product, then efforts to increase buying interest need to emphasize the innovation of the importance of the product, through various activities.Keywords: Product, Brand, Price and Interest of purchase.